Moral responsibility and the boundaries of community : power and accountability from a pragmatic point of view - Smiley, Marion (University of Chicago Press, 1992)
The question of responsibility plays a critical role not only in our attempts to resolve social and political problems, but in our very conceptions of what those problems are. Who, for example, is to blame for apartheid in South Africa? Is the South African government responsible? What about multinational corporations that do business there? Will uncovering the "true facts of the matter" lead us to the right answer? In an argument both compelling and provocative, Marion Smiley demonstrates how attributions of blame--far from being based on an objective process of factual discovery--are